2019
DOI: 10.1016/j.pedneo.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

SCID/NOD mice model for 5-FU induced intestinal mucositis: Safety and effects of probiotics as therapy

Abstract: Using SCID/NOD mice as a novel model for 5-FU induced intestinal mucositis, we find that probiotics Lcr35 and LaBi do not lead to bacteremia, can improve diarrhea and body weight, can restore jejunal crypt depth, and significantly inhibit cytokines TNF-α, IL-1β, IFNγ, IL-6, IL-4, IL-10, and IL-17.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 41 publications
(41 reference statements)
2
17
0
Order By: Relevance
“…In our previous study, we demonstrated that those mice in the 5-FU-induced intestinal mucositis group had significantly higher levels of circulating pro-inflammatory cytokines which decreased significantly after probiotic administration ( 26 ). We found similar results in using SCID/NOD mice as animal model, suggesting that innate immunity plays a role in the pathogenesis of intestinal mucositis ( 40 ). It seems that VD also exerts similar anti-inflammatory effects through the inhibition of pro-inflammatory cytokine expressions according to the results of this mouse model study.…”
Section: Discussionsupporting
confidence: 72%
“…In our previous study, we demonstrated that those mice in the 5-FU-induced intestinal mucositis group had significantly higher levels of circulating pro-inflammatory cytokines which decreased significantly after probiotic administration ( 26 ). We found similar results in using SCID/NOD mice as animal model, suggesting that innate immunity plays a role in the pathogenesis of intestinal mucositis ( 40 ). It seems that VD also exerts similar anti-inflammatory effects through the inhibition of pro-inflammatory cytokine expressions according to the results of this mouse model study.…”
Section: Discussionsupporting
confidence: 72%
“…Our previous research successfully demonstrated that Lactobacillus were associated with the maintenance of the tight junction integrity and appearance . These results shed light on the potential of probiotics to restore the dysbiosis of 5‐FU‐induced intestinal mucositis both in BALB/c and SCID/NOD mice models: repairing the jejunum, ameliorating diarrhea, and halting bodyweight loss . The exact mechanisms by which probiotics exert their beneficial effects remain unclear.…”
Section: Discussionmentioning
confidence: 74%
“…However, there were obvious bacterial translocations found in mesentery lymph node, and small amount bacterial number was found in liver. In our previous study, we found no evidence of strains in blood, liver, and spleen samples of BALB mice and SCID/NOD mice…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations